Effects of a fatty acid synthase inhibitor on adipocyte differentiation of mouse 3T3-L1 cells - LIU Li-hong; WANG Xiao-kui; HU Yuan-dong; KANG Jian-lei; WANG Li-li; LI Song (Acta Pharmacologica Sinica, 2016)
AIM: To investigate the influence of C75, a fatty acid synthase inhibitor, on adipocyte differentiation. METHODS: Mouse 3T3-L1 preadipocytes were induced to differentiation by insulin, isobutylmethylxanthine, and dexamethasone. Oil red O staining was performed and activity of glycerol-3-phosphate dehydrogenase (GPDH) was measured. The level of peroxisome proliferators-activated receptor gamma (PPARgamma) mRNA was assayed by semi-quantitative reverse transcription PCR. RESULTS: C75 blocked the adipogenic conversion in a dose-dependent manner and the inhibitory effects occurred both in the early phases (48 h) and in the latter phases (8 d) of the process. Treatment with C75 for 8 d induced more decrease in lipid content than 48 h (P